Investigating the impact of written emotion disclosure on the level of occupational stress among intensive care nurses - Jafariathar, Zahra; Haghighi, Shayesteh; Jahani, Simin; Maraghi, Elham (Frontiers in Psychology, 2023)
Objective: The present study was conducted with the aim of determining the impact of rewriting pleasant events on the level of occupational stress in ICU nurses. Methods: This is a quasi-experimental research conducted on nurses working in the intensive care units of Imam Khomeini and Golestan hospitals in Ahvaz, from July to November 2021. Seventy-six nurses were selected based on the inclusion criteria, and were then randomly assigned to the intervention and the control groups. The nurses’ demographic information form and the Expanded Nursing Stress Scale were used to collect data. In the intervention group, the technique of rewriting pleasant events was used for 8 weeks, at least once a week. The data was analyzed with SPSS V20. Results: No significant difference in the demographic characteristics was observed between the intervention and the control groups (P > 0.05). The pre-intervention occupational stress of the nurses in the intervention and the control groups were reported to be 173.86 ± 26.75 and 173.05 ± 24.47, respectively, showing no statistically significant difference (P = 0.89). After the intervention, the occupational stress scores were 134.21 ± 16.09 and 172.36 ± 24.33, respectively, showing a significant difference between the two groups (P < 0.001). Conclusion: Considering the impact of rewriting pleasant events on the level of occupational stress of ICU nurses, it is recommended that nursing managers and nurses plan training programs for nurses in this area, and encourage other nurses to do so, too. It is also suggested to implement this intervention on the nurses of other wards as well.